Numerical simulation of renewable power generation using reverse electrodialysis. (1st June 2019) - Chanda, Sourayon; Tsai, Peichun Amy
Abstract: We numerically investigate renewable power generation using reverse electrodialysis (RED), by harnessing salinity gradient energy of two constant inflows of salt solutions of different concentrations via a charged nanochannel. We compute and elucidate coupled flow, ion flux, electrical potential, and resultant electric outputs in the nanofluidic RED battery. The results of power output density and ion transfer across the nanochannel strongly depend on nanochannel height, whereas open-circuit voltage, short circuit current, and nanochannel resistance on the length. Energy conversion efficiency, on the other hand, display a non-linear dependence on both dimensions. More importantly, the results of nanochannel resistance and power output density reveal a power-law dependence on the concentration difference, quantitatively shedding light on the optimal RED flow designs. For the first time, our simulations at different inflow velocities show that the output power and conversion efficiency remain nearly constant at low speed but increase by ≈ 2.3 times and 10 %, respectively, at high rate when advection effect becomes significant comparing to diffusion. These results quantitatively show profound effects of nanochannel dimensions, concentration difference, and inflow velocity on the renewable electrical energy outputs, offering optimal designs for maximizing reverse electrodialysis power.